Pemberdayaan Pembentukan Kader Kesehatan melalui Pengembangan Inovasi Teknologi R-Care Menuju Masyarakat Sehat di Kelurahan Tanjung Pura Karawang - Erlena, Erlena; Sudiono, Sudiono (Carmin: Journal of Community Service, 2023)
The existence of public health around the Horizon University area is more than 5 km away, so that the community does not get easy access when they need health services. The initial survey obtained data on the highest prevalence of diseases such as hypertension, rheumatism, gout, diarrheal diabetes in children and respiratory infection disease. Therefore, the importance of developing R- Care technology innovation as a means of health service facilities that aims to realize a healthy society, prosperous and assist the community primarily in the first treatment. This activity consisted of empowering health cadres, disseminating knowledge about R-Care applications, and visiting a team of health workers for homecare services. The target group in this activity is the community in Tanjungpura area. The results of the activities are that people are familiar with online health services, The community has promoted horizon care services to the surroundings and has carried out visits in order to empower cadres for various R- Care services.